Teacher points to dyslexia as a major cause of school failure - Vicente Martins (Universidade Federal de Santa Catarina, 2002)
In the past seven years, Professor Vincent Martins has developed studies on the contribution of linguistics to the diagnosis of dyslexia. The dyslexia is a disturbance or inconvenience to the level of reading. The dyslexic children is a bad player: you can read but can not effectively understand what you read. The estimate of the teacher is that, in Brazil at least 15 million children and young people suffering with disorders of letters. For the teacher, the dyslexia is the major cause of low school performance.